From Praha to Prague : Czechs in an Oklahoma farm town - Smith, Philip D. (2017)
" Around the turn of the twentieth century, thousands of Czechs left their homelands in Bohemia and Moravia and came to the United States. While many settled in major American cities, others headed to rural areas out west where they could claim their own land for farming. In From Praha to Prague, Philip D. Smith examines how the Czechs who founded and settled in Prague, Oklahoma, embraced the economic and cultural activities of their American hometown while maintaining their ethnic identity. According to Smith, the Czechs of Prague began as a clannish group of farmers who participated in the 1891 land run and settled in east-central Oklahoma. After the town's incorporation in 1902, settlers from other ethnic backgrounds swiftly joined the fledgling community, and soon the original Czech immigrants found themselves in the minority. By 1930, the Prague Czechs had reached a unique cultural, social, and economic duality in their community